MODL-18. ORGANOTYPIC BRAIN SLICE CULTURES: A COMPREHENSIVE MODEL FOR PRIMARY CNS TUMOR STUDIES. (14th November 2022) - Reid, Alexandra
Abstract: Inducing an immunosuppressive environment has been one of the most notable subversive tactics employed by aggressive primary brain tumors like Glioblastoma (GBM). It is vital that we garner a better understanding of the cell-cell interactions occurring within the tumor microenvironment (TME) in situ . Current in vitro and in vivo models sorely limit our ability to study the cell-cell interactions within the TME while accounting for its complexity and the spatial orientation of its components. Unfilled, this gap in physiologically relevant models greatly hinders the translation of impactful research findings to successful treatment options for patients diagnosed with GBM and other primary CNS tumors. We have devised a novel organotypic brain slice culture (BSC) model study using tumor-bearing C57BL/6J mice which brings the potential to not only determine the cell-cell interactions within the TME but also investigate the underlined mechanisms which govern them. Obtaining BSCs from tumor-bearing mice at various time points post-implantation also allows for analysis of the trafficking of various immune cells across the blood-brain barrier (BBB). We demonstrated outcomes similar to those seen in vivo following the introduction of parallel conditions, further supporting the physiological relevancy of this model. Thus, organotypic brain slice cultures from tumor-bearing mouse models may serve as a credible and incredibly versatile model for the study of primary CNS tumors which may bridge the gap between in vitro and in vivo studies.